PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA KANTOR CAMAT KECAMATAN MARO SEBO ILIR - Etty Siswati (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
The purpose of this research is to: 1) To know the organizational culture at the Office of the head of the subdistrict Maro Sebo Ilir; 2) to work on the discipline Office Camat Kecamatan Maro Sebo ilir; 3) To know the influence of the culture of the Organization and discipline work against the performance of the employees of the Office of the head of the subdistrict Maro Sebo Ilir. Data collection methods used in this survey method is used to obtain information from respondents using interview techniques and disseminate a list of questions as well as using the likert scale measurements. Data analysis tools are used multiple regression is a method using computer assistance through the program SPSS 20.0 for windows. The results of the analysis showed. Variable Buduya Organization thitung ttabel 3,320 > value ttable 169726 means the organizational culture positive significant effect against the performance of civil servants in the Office of the head of the subdistrict Maro Sebo Ilir. Variable Working Discipline (X2) value thitung ttable 169726 > 3,108 Disciplined work means a positive significant effect against the performance of civil servants in the Office of the head of the subdistrict Maro Sebo Ilir. The F-test is used to determine whether the variable X1 (organizational culture) and X2 (the discipline of work) can affect the Y (Employee Performance) simultaneously (simultaneous). distribution of F in df = 33 of 3.28, this means that the value of Fhitung > value Ftable (39.901 > 3.28), and significant value 0.000 < 0.06 then follows the variable X1 (organizational culture) and X2 (the discipline of work) the simultaneous and significant effect against Y (Employee Performance) at the head of the subdistrict Office Maro Sebo Ilir. The coefficient of Determination is used to find the percentage of independent variable influences the dependent variables against. Adjusted R2 value of 0.709 in statistics show the value of influence in percentage or relative free variables used in this study i.e. organizational culture (X1) and discipline work (X2) against the variable performance employees (Y). the value of 0.709 means 70.9% employee performance (Y) at the Office of the head of the subdistrict Maro Sebo Ilir is influenced by organizational culture (X1) and discipline work (X2). The rest amounted to 29.1% is affected by factors or other variables that are not included in this researchKeywords: organizational culture, work discipline and performance.